2012
DOI: 10.1126/science.1227621
|View full text |Cite
|
Sign up to set email alerts
|

Driving a Macroscopic Oscillator with the Stochastic Motion of a Hydrogen Molecule

Abstract: Energy harvesting from noise is a paradigm proposed by the theory of stochastic resonances. We demonstrate that the random switching of a hydrogen (H(2)) molecule can drive the oscillation of a macroscopic mechanical resonator. The H(2) motion was activated by tunneling electrons and caused fluctuations of the forces sensed by the tip of a noncontact atomic force microscope. The stochastic molecular noise and the periodic oscillation of the tip were coupled in a concerted dynamic that drives the system into se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 32 publications
2
41
1
Order By: Relevance
“…The other strong signals found at ±17 meV for H 2 in the IETS spectrum are due to conformational switching of the molecule in the tunnel junction. [11][12][13][14][15][16][17][18][19][20][21] As previously mentioned, the energy of the switching is extremely sensitive to coverage, tip state, and tipsurface separation. [17][18][19][20][21] There are also inelastic peaks around ±4 meV for H 2 .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The other strong signals found at ±17 meV for H 2 in the IETS spectrum are due to conformational switching of the molecule in the tunnel junction. [11][12][13][14][15][16][17][18][19][20][21] As previously mentioned, the energy of the switching is extremely sensitive to coverage, tip state, and tipsurface separation. [17][18][19][20][21] There are also inelastic peaks around ±4 meV for H 2 .…”
mentioning
confidence: 91%
“…[22,23] This was the first demonstration of H 2 rotational spectra on a bare metal surface by IETS, which raises the question of what makes Au(110) a more suitable substrate than Cu(111), [ 17,18] Ag(111), [19] or nanojunctions made of various metals. [9][10][11][12][13][14][15][16] It is also unclear if rotational IETS probes single molecules or molecular ensembles.…”
mentioning
confidence: 99%
“…The separation of energy in heat and useful work and dissipation is the key for a thermodynamical description. In quantum systems under ac driving, the identification of these different components of energy is a nontrivial task which is paramount to cold atoms [1], nanomechanical [2,3], nanoscale optoelectronical [4], and mesoscopic electron physics [5][6][7][8][9][10][11][12][13][14][15][16]. Typically, the central piece of these systems contains a small number of particles and are driven out of equilibrium, which renders a usual thermodynamical description unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly applied to reduce organic compounds in multiple fields ranging from pharmaceutical, electronics, to green energy applications. [11][12][13] As the smallest molecule, H 2 is ideal for probing the properties of nano-reactors. Previous STM studies have revealed that the adsorption of H 2 on metal surfaces is extremely weak, mainly via the van der Waals forces.…”
mentioning
confidence: 99%